2020
DOI: 10.1002/aqc.3340
|View full text |Cite
|
Sign up to set email alerts
|

Sound features and vocal rhythms as a proxy for locating the spawning ground ofSciaena umbrain the wild

Abstract: The brown meagre (Sciaena umbra) is a demersal sciaenid fish recognized as indicative of good environmental quality and is defined as an umbrella species for the ecological community of rocky coastal habitats. Sciaena umbra is classified as a Vulnerable fish species by the International Union for Conservation of Nature (IUCN) and knowledge on the distribution of its spawning habitats is essential for its conservation. Passive acoustic monitoring (PAM) is a suitable tool to monitor S. umbra distribution becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 66 publications
3
24
0
Order By: Relevance
“…Pereira et al (2020) found that Q3 frequency is dependent on individual size [ 42 ]; fish at HCMR were bigger than fish at IPMA, which may explain this statistical significance. When it comes to temporal features, Bolgan et al [ 43 ] showed that meagre sound duration, number of pulses and pulse period are influenced by spawning motivation; this is in accordance with what was found in other Sciaenidae species, in aquaculture as well as at sea [ 43 , 65 67 ]. At HCMR, spawning was artificially induced by injecting gonadotropin releasing hormone agonist (GnRHa), while fish at IPMA spawned naturally.…”
Section: Discussionsupporting
confidence: 71%
“…Pereira et al (2020) found that Q3 frequency is dependent on individual size [ 42 ]; fish at HCMR were bigger than fish at IPMA, which may explain this statistical significance. When it comes to temporal features, Bolgan et al [ 43 ] showed that meagre sound duration, number of pulses and pulse period are influenced by spawning motivation; this is in accordance with what was found in other Sciaenidae species, in aquaculture as well as at sea [ 43 , 65 67 ]. At HCMR, spawning was artificially induced by injecting gonadotropin releasing hormone agonist (GnRHa), while fish at IPMA spawned naturally.…”
Section: Discussionsupporting
confidence: 71%
“…16-27 ms (Picciulin et al, 2012;Parmentier et al, 2018). All of these features have been proved to be consistent over space and time, despite the fact that intra-specific variation depends on context, size and motivation or the influence of recording settings and conditions (Parmentier et al, 2018;Picciulin et al, 2020).…”
Section: Sounds Characterization Detection and Discriminationmentioning
confidence: 90%
“…At sea the FSAs of vocal species can generate intense choruses that greatly exceed local ambient noise levels (Parsons et al, 2016;Rice, Soldevilla & Quinlan, 2017). Fish choruses have been used as proxies to determine the timing and location of spawning aggregations, as well as for evaluating species distributions and essential habitats (Luczkovich et al, 2008;Tellechea et al, 2010b;Rice, Soldevilla & Quinlan, 2017;Monczak et al, 2019;Picciulin et al, 2020). Furthermore, the sound level of fish choruses provides insights into fish population abundances (Rowell et al, 2012;Rowell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations